ANALISIS TINGKAT KEPUASAN BERDASARKAN PERSEPSI PENGUNJUNG DI KAWASAN EKOWISATA MANGROVE PARK BAHOWO KOTA MANADO SULAWESI UTARA - Safrin Radeng; Wawan Nurmawan; Fabiola B. Saroinsong (Universitas Sam Ratulangi, 2019)
ABSTRACT The purpose of this study was to analyze the level of visitor satisfaction based on perceptions in the Mangowo Park Bahowo ecotourism area (MPB). The availability of information about the level of visitor satisfaction with the ecotourism area is expected to be an evaluation material for the manager in preparing the Mangrove Park Bahowo ecotourism development plan. This research was conducted in August-September 2019 in Bahowo, Tongkaina Village, Manado City. This research was conducted through a survey by filling out a questionnaire through interviews with 30 respondents. The data obtained were analyzed using the Likert Scale method. Based on the results of the study, the researchers concluded that MPB's natural beauty received the highest perception rating, which affected the level of visitor satisfaction giving the highest score on MPB view quality. The lowest level of visitor satisfaction for a variety of attractions, is related to the low visitor perceptions of ecotourism facilities and their arrangement.